A Decade of Growth: From Social Media to Academic Friendship - Yeyentimalla, Yeyentimalla; Christyanni, Yuyun; Suryawati, Sri (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: Friendship is a safe relationship in which individuals can express various facets of themselves. A true friend allows another to be fully themselves in their presence, resulting in personal growth and progress – not only for individuals, but also for institutions, society, and the nation. A friendship that began as a student-teacher relationship and has lasted a decade (2015-2025) was lived, observed, and reflected upon. Aims: This photo essay aims to explore how an intially asymmetric relationship between student and teacher gradually grew into an academic friendship. It is intended to inspire readers to nurture safe and trusting connections within their own circles. Methods: This case study investigates a student-teacher friendship relationship, highlighting learning points worth sharing publicly. The relationship consciously incorporated emotional communication – emotional intelligent interaction that engages feeling-based expression and empathetic simulation. Results: A bond that began between two strangers on Facebook evolved into an academic friendship, then into a student-examiner relationship during doctoral study. After the doctoral journey ended, the connection reverted to a stronger friendship. This relationship yielded collaborative works and programs that have benefited both Indonesian and global communities. Conclusion: This case study offers several takeaways on building meaningful friendship that foster personal growth and benefit the wider environment.